Dual Electroactivity in a Covalent Organic Network with Mechanically Interlocked Pillar[5]arenes. Issue 37 (19th May 2021) - Colasson, Benoit; Devic, Thomas; Gaubicher, Joël; Martineau‐Corcos, Charlotte; Poizot, Philippe; Sarou‐Kanian, Vincent
Abstract: The synthesis and characterization of a polyrotaxanated covalent organic network (CON) based on the association between the viologen and pillar[5]arene (P[5]OH) units are reported. The mechanical bond allows for the irreversible insertion of n‐type redox centers (P[5]OH macrocycles) within a pristine structure based on p‐type viologen redox centers. Both redox units are active on a narrow potential range and, in water, the presence of P[5]OH greatly increases the electroactivity of the material. Abstract : Redox active pillar[5]arene macrocycles are inserted via mechanical bonds in a viologen‐based covalent organic network. Solid state electrochemical studies show that both n and p type redox centers are active on a relatively narrow potential range (∼1 V). The presence of the pillar[5]arene macrocycles boosts the electroactivity of the solid in aqueous electrolyte.